Pemasaran Pendidikan Menuju Era Revolusi Industri 5.0 - Fajri Dwiyama (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2021)
The development of the world of education is so rapid, in proportion to the level of competition between educational institutions. This happened due to a paradigm shift towards the views of educational experts who initially looked at the social aspect of society and turned to corporate. Educational institutions are not only seen as a forum for producing superior human resources, but beyond that. Educational institutions grow into production organizations that produce products and services offered to consumers. The use of assistive devices in the form of technology also contributes greatly to the marketing of education carried out by institutions. Technological sophistication allows educational institutions to expand the marketing area in an unlimited and seamless direction. However, behind this various problems have emerged in the management of educational institutions related to marketing competition. Educational institutions that master technology can market well will get a high response from the community, on the other hand institutions that do not have the ability to master technology in supporting marketing will be left behind and abandoned by the community.